Au-decorated WO3 cross-linked nanodomes for ultrahigh sensitive and selective sensing of NO2 and C2H5OH - Shim, Young-Seok; Moon, Hi Gyu; Kim, Do Hong; Zhang, Lihua; Yoon, Seok-Jin; Yoon, Young Soo; Kang, Chong-Yun; Jang, Ho Won (ROYAL SOC CHEMISTRY, 2013)
Au-decorated WO3 cross-linked nanodomes are fabricated using soft templates composed of highly ordered polystyrene beads and self-agglomeration of Au. The distribution and size of Au nanoparticles on the surface of WO3 cross-linked nanodomes are controlled by varying the thickness of the initial Au film. The responses of Au-decorated WO3 cross-linked nanodomes to various gases such as NO2, CH3COCH3, C2H5OH, NH3, CO, H-2, and C6H6 are at least 5 times higher than those of bare WO3 cross-linked nanodomes. The response enhancement by Au decoration is dependent on the target gas, which is attributed to an interplay between electronic and chemical sensitizations. In particular, the Au-decorated WO3 cross-linked nanodomes exhibit extremely high sensitivities and selectivities, and ppt-level detection limits to NO2 and C2H5OH at 250 degrees C and 450 degrees C, respectively. These results suggest that Au-decorated WO3 cross-linked nanodomes are very promising for use in breath analysers to diagnose both asthma and lung cancer from exhaled human breath.
Keywords: SEMICONDUCTOR GAS SENSORS; SURFACE-CHEMISTRY; ELECTRONIC NOSE; EXHALED BREATH; LUNG-CANCER; THIN-FILMS; GOLD; CATALYSIS; NANORODS; CLUSTERS